2017
DOI: 10.1002/aenm.201602733
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal (Fe, Co, Ni) Based Metal‐Organic Frameworks for Electrochemical Energy Storage

Abstract: Transition‐metal (Fe, Co, Ni) based metal‐organic framework materials with controllable structures, large surface areas and adjustable pore sizes have attracted wide research interest for use in next‐generation electrochemical energy‐storage devices. This review introduces the synthesis of transition‐metal (Fe, Co, Ni) based metal‐organic frameworks and their derivatives with the focus on their application in supercapacitors and batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
327
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 797 publications
(338 citation statements)
references
References 204 publications
1
327
0
3
Order By: Relevance
“…[28] Therefore, it is necessary to optimize and improve the electrochemical performance of the battery by studying the reaction mechanism. [33][34][35][36][37][38][39][40] The inadequacies are also obvious, including volume expansion, agglomeration, low ion-diffusion coefficient, and side reaction during discharge/charge, resulting in the rapid decay of capacity. [33][34][35][36][37][38][39][40] The inadequacies are also obvious, including volume expansion, agglomeration, low ion-diffusion coefficient, and side reaction during discharge/charge, resulting in the rapid decay of capacity.…”
mentioning
confidence: 99%
“…[28] Therefore, it is necessary to optimize and improve the electrochemical performance of the battery by studying the reaction mechanism. [33][34][35][36][37][38][39][40] The inadequacies are also obvious, including volume expansion, agglomeration, low ion-diffusion coefficient, and side reaction during discharge/charge, resulting in the rapid decay of capacity. [33][34][35][36][37][38][39][40] The inadequacies are also obvious, including volume expansion, agglomeration, low ion-diffusion coefficient, and side reaction during discharge/charge, resulting in the rapid decay of capacity.…”
mentioning
confidence: 99%
“…Traditionally, PC can be obtained via various methods, such as the direct heat treatment of organic precursors, hard template or nanocast methods, and soft template methods. [4,21,[27][28][29][30][31] Since the report on the MOF-templated synthesis of PC in 2008, [32] a large number of studies have been reported on the use of MOFs as suitable precursors/templates for carbon synthesis. [23,25,26] Metal-organic frameworks (MOFs) have drawn wide research interest as a novel class of porous materials that are crystalline materials consisting of metal ions and organic ligands.…”
mentioning
confidence: 99%
“…Given the rapid development of portable electronics, electric vehicles, and smart grids, advanced electrochemical energy storage systems have been investigated extensively [1][2][3][4][5][6][7][8][9][10][11]. Lithium-sulfur (Li-S) batteries are expected to perform a significant role in the field of energy storage owing to its ultrahigh theoretical energy density of 2500 Wh kg −1 , environmental friendliness, and low cost [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%